Hepatitis B vertical transfer and its risk factors in pregnant women in the eastern part of Iran - Moghadam, M.N.; Amirian, S.; Afshari, M.; Parooie, F.; Keikhaie, K.R.; Shahramian, I.; Bazi, A.; Ostadrahimi, P.; Sheikh, M.; Mirzaie, H.; Aminisefat, A. (Medicni Perspektivi, 2022)
One of the main causes of chronic hepatitis is mother to child transfer which is also known as vertical transfer (VT). Although there are several studies regarding the VT mechanism and its risk factors, none of these studies succeeded in explaining this process, completely. We conducted this study aiming at investigating VT mechanism and risk factors in this region. The present study was a descriptive-analytic cross-sectional study on HBS Ag positive pregnant women, which was conducted from March 2018 to March 2020 in Amir-Al-Momenin Hospital in Zabol, Sistan-and-Baluchestan province, Iran. In this study all samples were tested for HBV markers (HBsAg, anti-HBs, HBeAg, anti-HBe, anti-HBc, and HBV-DNA) and anti-HCV by enzyme-linked immunosorbent assay (ELISA). All statistical analyzes were performed using SPSS version 22 software. Totally 43 infants of HBS antigen positive mothers were investigated. HBe antibody and HBe antigen were found in 25 (62.5%) and 2 (5%) of mothers, respectively. There was no significant difference between the newborns with and without hepatitis B infection regarding maternal age (p=0.216), duration of the infection in mother (p=0.892), AST (0.779), AL (0.449) and ALP (0.065). Mothers with positive viral load during pregnancy delivered newborns with positive HBS antigen much more than mothers with negative HBS antigen. However, this difference was not statistically significant (p=0.642). Although positive viral load was more common in neonates delivered from positive viral load mothers, the observed difference was also remained non-significant (p=0.978). Our study provided evidences regarding that demographic, immunologic and clinical characteristics of mothers with hepatitis B infection did not play considerable role in the vertical transmission of the infection to the newborns as well as the severity of the following infection. We also suggested the possibility of placenta acting as a source of infection in VT. Further longitudinal studies with larger sample sizes are needed to show the exact predictors of transmission of the infection from infected mothers to their children.